Servant Leadership, Organizational Culture, And Employee Performance: Examining The Mediating Role of Job Satisfaction at The Regional Revenue Agency of Riau Province - Windi Desvianti; Abd. Rasyid Syamsuri; Rosnelly Roesdi (International Journal of Science and Environment (IJSE), 2026)
This study examines the effects of servant leadership and organizational culture on employee performance, with job satisfaction acting as a mediating variable, among employees of the Regional Revenue Agency of Riau Province, Indonesia. A quantitative research approach was employed using survey data collected from 58 employees selected from a population of 118 employees through the Slovin formula. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) and Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings reveal that servant leadership and organizational culture have positive and significant effects on both job satisfaction and employee performance. Furthermore, job satisfaction has a positive and significant effect on employee performance and significantly mediates the relationships between servant leadership and employee performance as well as between organizational culture and employee performance. These findings highlight the importance of strengthening servant leadership practices and fostering a supportive organizational culture to enhance employee satisfaction and ultimately improve employee performance in public sector organizations.